A meta-analysis of cross-sectional studies on the frequency and risk factors associated with canine morbillivirus infection in China. (December 2021) - Dong, Bo; Zhang, Xiaodong; Wang, Jincong; Zhang, Gaoqiang; Li, Chengyu; Wei, Lan; Lin, Weiming
Abstract: Background: The canine morbillivirus, previously known as canine distemper virus (CDV), is a pathogen which infects dogs worldwide and causes fatal disease. CDV has a broad range of hosts and can infect at least six orders and more than 20 mammalian families. Domestic dogs are the main hosts of CDV and play a central role in the transmission of the virus. However, the prevalence of CDV infection in China remains unknown since there are only a few studies which systematically analysed the prevalence of CDV in domestic dogs in the country. Therefore, we conducted a systematic review and meta-analysis of the frequency of CDV positivity and associated risk factors of CDV in Chinese domestic dogs. Methods: We systematically searched for studies on the frequency of CDV in Chinese domestic dogs published in English and Chinese to conduct a meta-analysis using the random-effects model with a forest plot with a 95% confidence interval. Results: The overall estimated frequency of CDV positivity in Chinese domestic dogs was 22%. In addition, our data show that sampling season, age, breed, and immunisation status are associated with CDV infection frequency. Conclusion: In a word, CDV is circulating in domestic dogs in China. Continued intervention strategies based on risk factors are necessary to reduce the frequency of CDV infection, especially in endemic regions. Highlights: CDV is prevalent in domestic dogs in China. CDV is infectious throughout the year especially during spring. A dog's age, breed and immunisation status are associated with CDV infection prevalence. Continued intervention strategies for CDV based on risk factors are necessary.